2017
DOI: 10.1002/adma.201605744
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Detection in Tumor Cell Cultures Using Organic Transistor Circuits

Abstract: A biosensing platform based on an organic transistor circuit for metabolite detection in highly complex biological media is introduced. The sensor circuit provides inherent background subtraction allowing for highly specific, sensitive lactate detection in tumor cell cultures. The proposed sensing platform paves the way toward rapid, label-free, and cost-effective clinically relevant in vitro diagnostic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
126
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 34 publications
0
126
0
1
Order By: Relevance
“…6 and 7 experienced large Stokes shifts indicating that the excited-state molecules display a more planar conformation or a more pronounced charge-transfer state before emission. Bulk heterojunction inverted photovoltaics with the configuration of ITO/Ca/BODIPY dyes: [6,6]-phenyl C71 butyric acid methylester (PC 71 BM) (1 : 3, w/w)/MoO 3 /Ag were fabricated by spin-casting the active layer from chloroform solution. Different concentrations of the dyes were applied for the active layer; the resulting varied film thickness was found to play an important role in determining the electrical characteristics of the device.…”
Section: Semiconductors With a Central Bodipy π-Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and 7 experienced large Stokes shifts indicating that the excited-state molecules display a more planar conformation or a more pronounced charge-transfer state before emission. Bulk heterojunction inverted photovoltaics with the configuration of ITO/Ca/BODIPY dyes: [6,6]-phenyl C71 butyric acid methylester (PC 71 BM) (1 : 3, w/w)/MoO 3 /Ag were fabricated by spin-casting the active layer from chloroform solution. Different concentrations of the dyes were applied for the active layer; the resulting varied film thickness was found to play an important role in determining the electrical characteristics of the device.…”
Section: Semiconductors With a Central Bodipy π-Unitmentioning
confidence: 99%
“…[1] This breakthrough in 1970s has clearly revealed that organic compounds could transport electric current by proper molecular design and controlled doping, and, as a result, organic (semi)conductors have become the key components in organic (opto)electronic devices, especially in organic thin-films transistors (OTFTs) and organic photovoltaics (OPVs). [2][3][4][5][6][7][8][9][10][11] Thanks to the advancements in the past four decades in the design and development of organic semiconductors, OTFTs have emerged as an alternative technology to conventional transistors for cost-effective, large-area, printable, and flexible electronics, [12][13][14][15][16][17][18][19][20][21] and OPVs have emerged as a viable source of low-cost renewable energy with zero carbonemission in everyday life. OPVs are also envisioned to address numerous environmental issues mainly caused by fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Although metabolite detection has extended to low mM concentrations, there is usually undesirable electrochemical interference from endogenous electroactive components in the electrolyte (i.e., cell culture media, bio‐fluids, and so on) thus hindering its practical implementation to some extent. One solution has been to design reference sensors alongside the metabolite sensor to subtract the real baseline (Braendlein et al, ) complicating the design of the sensor. Therefore, developing methods that do not rely solely on the electrical readout of the device while still benefiting from the CP properties and its mixed conductivity, can open new directions in molecular sensing in terms of specificity and sensitivity as well as provide straightforward paths toward their real‐world implementation (A.‐M.…”
Section: Introductionmentioning
confidence: 99%
“…OECT technology is also compatible with brightfield and fluorescence high-resolution microscopy as the PEDOT:PSS active layer is optically transparent 35 . Notably, the OECT has also been demonstrated for highly sensitive and specific metabolite sensing from complex media, through biofunctionalization of the gate electrode 26,30,[36][37][38] .…”
Section: Introductionmentioning
confidence: 99%